Karakteristik Kimia dan Sensori Susu Pasteurisasi Berdasarkan Penambahan Susu Skim Bubuk: Characteristics of Pasteurized Milk with the Addition of Skim Milk Powder - Juwina, Siti nurul; Kurniawan, Muhammad Fakih; Nurhalimah, Siti (Jurnal Ilmiah Pangan Halal, 2025)
This study aimed to evaluate the effect of skim milk powder addition on the chemical and sensory quality of pasteurized milk. The treatments consisted of concentrations of 0%, 2%, 4%, and 6%. The chemical parameters analyzed included protein, fat, total solids, pH, and total acidity, while sensory evaluation covered scoring and hedonic tests on color, aroma, taste, and texture. Data were analyzed using ANOVA followed by Duncan’s test. The results showed that the addition of skim milk powder increased protein and total solids, decreased fat, lowered pH, and increased total acidity. Sensory evaluation revealed significant differences in taste with the highest mean score of 6.83 (6%) indicating a more distinctive milk flavor, and in texture with the highest mean score of 6.50 (6%) indicating a thicker consistency, while color and aroma showed no significant differences. Panelists preferred the 2% treatment for color and the 4% treatment for taste. Therefore, the addition of skim milk powder can improve the chemical quality and certain sensory attributes of pasteurized milk.